(untitled) (Research, Society and Development, 2022)
Objective: to verify in the literature the perception of nursing professionals about the importance of palliative care in the oncological field. Method: this is an integrative review. The search for articles was carried out in the Virtual Health Library (BVS), in an advanced search for the terms ’’oncology’’ and ’’palliative care’’ and ’’nursing’’, resulting in the selection of 21 scientific articles. Results: The care of the nursing team needs a subjective look, valuing beyond the signs and symptoms felt by the patient and family, but seeking to value spirituality, family support, communication, among other aspects. The way of caring must be developed from a global process, which involves the being as a whole so that the patient is considered as a biopsychosocial and spiritual individual, within ethical and moral values. However, nursing training is often focused only on technical and practical actions, and subjective issues are not deepened in the academic environment, causing the emotional side of professionals to not be practiced during care. Final considerations: Through this study, it was possible to understand the knowledge, skills, and indispensable perceptions that the nursing team needs to have to provide palliative care properly.